Sistem Absensi Karyawan Secara Realtime Berbasis Fingerprint Menggunakan Metode Rapid Application Development - Fullchis Nurtjahjani; Joni Dwi Pribadi; Kadek Suarjuna Batubulan; Milyun Ni’ma Shoumi (Universitas Diponegoro, 2022)
The role of human resources (employees) in the company is very important because it functions as the main driver of all activities of the company in achieving its goals. One of the things that can affect employee performance is the number of wages given by the company. The number of wages given by the company to employees can be determined, one of which is through the presence of employees in one month. Therefore, employee attendance data is something that is very important for a company. However, some companies still recap attendance, calculate overtime hours, and make employee attendance reports manually. This work is certainly less effective because it requires a lot of time and effort, where the results are not necessarily accurate, so there is often unrest, dissatisfaction and injustice in the provision of employee wages. Therefore, we need a system that can recapitulate employee attendance hours automatically. This study aims to build an attendance system and calculate employee overtime hours in real time based on employee attendance through fingerprints, as well as conduct trials and evaluations of the attendance system created. The process of managing employee attendance data can be done through a website-based information system by implementing the Rapid Application Development (RAD) method. The attendance information system has been developed to be implemented at PT. Sriwijaya Delapan Tujuh Malang, and based on the results of testing through a questionnaire, the system is easy to use and can help the process of providing employee wages through the results of a recap of attendance and overtime every day.